SOCIAL AND LEGAL PREVENTION OF CRIMES AND OFFENSES OF ORPHANS IN BOARDING SCHOOLS: ON THE EXAMPLE OF THE KEMEROVO REGION - Artyom Y. Nesterov (Scientific Journal of Pedagogy and Economics, 2021)
The article is devoted to one of the urgent problems, such as social and legal prevention of delinquency of orphans in boarding schools in the Kemerovo region. To date, the problem of legal impact on a child is primarily due to the fact that it achieves the ultimate goal of all legal regulation - the implementation of legal prescriptions in the life of every teenage orphan who is in a boarding school. Today in Russia the historical and socio-demographic situation has developed in such a way that the reform of Russian society has been accompanied and accompanied by a fairly widespread criminalization of various spheres of public life. Involvement in illegal activities of large and small social groups also affected minors-orphans who are in boarding schools of the Kemerovo region, as the most sensitive stratum of Russian society, involvement in illegal activities of large social groups, also affected minors - orphans as the most sensitive part of the population in relation to transformational changes taking place in modern society. Today, prophylactic work is being actively carried out with orphaned children in boarding schools in the Kemerovo Region - this is a complex, multidimensional, long-term process. The specific task of the boarding school for orphans in the field of crime prevention is to carry out early prevention, that is, to create conditions that ensure the possibility of normal development for the students of orphans. The presented material in the publication does not contain information related to the state secret of the Russian Federation.